Pengembangan Komik Digital “Aku Anak Sholehah, Aku Berempati” sebagai Media Pembelajaran PAI Siswa Kelas 2 Sekolah Dasar - Widi Prastika, Deninggar; Mazidah, Ninik; Fahri Ali, Muhammad; Putranta, Himawan (QuranicEdu: Journal of Islamic Education, 2024)
This article examines the problems that arise from technological advances that have a major impact on the world of education. Continuously developing technology has changed the way learning media are used and reduced students' interest in literacy. Literacy interest is a key element in the learning process, especially at the elementary school level. To overcome educational challenges in the 21st century, researchers developed digital comic learning media "I'm a Sholehah Child, I'm Empathetic". This media is designed to increase understanding of educational technology from an Islamic perspective, especially regarding the use of digital comic learning media which contains moral material in PAI subjects in grade 2 of elementary school. This research uses the Design & Development (D&D) method. This research was shared with colleagues, namely UIN Sunan Kalijaga students, by submitting a questionnaire via Google Form. This learning media is considered very suitable from various aspects, including appearance, teaching materials, learning and materials. This is proven by the results of a questionnaire filled out by colleagues from UIN Sunan Kalijaga, which shows that this media is very suitable for learning for grade 2 elementary school students.